Cancer worry and empathy moderate the effect of a survivorship‐focused intervention on quality of life. Issue 6 (11th March 2020) - Parker, Patricia A.; Banerjee, Smita C.; Matasar, Matthew J.; Bylund, Carma L.; Schofield, Elizabeth; Li, Yuelin; Jacobsen, Paul B.; Astrow, Alan B.; Leventhal, Howard; Horwitz, Steven; Kissane, David
Abstract: Objective: This study examined the impact of a survivorship planning consultation (SPC) for patients with Hodgkin's lymphoma and diffuses large B‐cell lymphoma on quality of life (QOL). We specifically assessed two potential moderators, cancer worry and perceived empathy, of the intervention effects on QOL. Methods: This cluster randomized, four‐site trial examined the efficacy of a SPC; physicians received communication skills training and applied these skills in a survivorship‐focused office visit using a care plan vs a control arm in which physicians were trained to and subsequently provided a time‐controlled, manualized wellness rehabilitation consultation focused only on discussion of healthy nutrition and exercise. We examined the effect of the intervention on patients' QOL and examined potential moderators—cancer worry and perceived physician empathy. Results: Forty‐two physicians and 198 patients participated. There was no main effect of the intervention on any of the QOL dimensions (ps > 0.10). However, cancer worry was a significant moderator of the effects of the intervention on three QOL domains (physical P = .04; social P = .04; spiritual P = .01) and perceived empathy was a significant moderator of QOL (physical P = .004; psychological P = .04; social P = .01). Specifically, the beneficial effects of the intervention were more pronounced among patients who initially reported higher levels of cancer worry and lower levels of physician empathy. Conclusions: This study identified two factors, perceived empathy and cancer worry, that were found to impact the QOL of patients who participated in this communication‐based survivorship intervention.